2007
DOI: 10.1007/s10661-006-9334-2
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Controls on Mercury in Streamwater at Acadia National Park, USA

Abstract: Fall and spring streamwater samples were analyzed for total mercury (Hg) and major ions from 47 locations on Mount Desert Island in Maine. Samples were collected in zones that were burned in a major wildfire in 1947 and in zones that were not burned. We hypothesized that Hg concentrations in streamwater would be higher from unburned sites than burned watersheds, because fire would volatilize stored Hg. The Hg concentrations, based on burn history, were not statistically distinct. However, significant statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Dissolved organic carbon binds Hg, assisting in its transport from neighboring wetlands to the lake and increasing bioavailability for methylation [31].…”
Section: Food Web Applicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Dissolved organic carbon binds Hg, assisting in its transport from neighboring wetlands to the lake and increasing bioavailability for methylation [31].…”
Section: Food Web Applicationsmentioning
confidence: 99%
“…Peckenham et al [31] found that wetlands mobilized more Hg from watershed than uplands by producing more DOC, even though upland could transport more Hg per unit of DOC.…”
Section: Food Web Applicationsmentioning
confidence: 99%
See 3 more Smart Citations